Static stress analysis of membrane electrode assembly (MEA) and gasket in Proton exchange membrane fuel cell stack assembly pressure - Edy Herianto Majlana,; Wan Ramli Wan Daud,; Teuku Husaini,; Masli Irwan Rosli,; Abu Bakar Sulong,; Mohd Shahbudin Mastar,; Darwin Sebayang,; Nurato.Nurato, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The proton exchange membrane fuel cell (PEMFC) system was an electrochemical device that generates electricity through the reaction of hydrogen and oxygen without combustion. Proton Exchange Membrane (PEM) stacks typically consisted of components combined into one unit and equipped with suitable clamping torque. This was to prevent reactant gas leakage and minimize the contact resistance between the gas diffusion medium and the bipolar plate. The combined components consisted of a bipolar plate with a flow field, current collector, membrane electrode assembly (MEA), endplate, and gasket. PEMFC performance was measured concerning its power output, which depends on temperature and the operating pressure. Various efforts had been made to determine the optimal compaction pressure and its distribution through simulations and experiments. Therefore, this research analyzed the static stress of membrane electrode assembly (MEA) and gasket in PEMFC stack assembly pressure. The components’ geometric dimensions and mechanical properties, such as endplates, current collectors, bipolar plates, MEAs, and gaskets, were combined for electricity. Pressure-sensitive film (Fuji measure film prescale) was also used to visualize contact pressure distribution between the MEA and the bipolar plate. The result showed that the color variation of the pressure film indicates the exact distribution of pressure entering the stacking design and the contact image. In conclusion, the detailed contact pressure distribution was an important influence on heat transfer processes and local electrochemical reactions in cell stacks.